The Role of Faith in Overcoming Mental Health - Erny Fitroh Nabila Muwafiqi; Achmad Khudori Soleh (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
Faith has only been interpreted theologically, namely belief in God. Even though only believing in the oneness of the substance, nature, and deeds of God without saying it verbally and without practicing deeds cannot be said to be a person with perfect faith. The research method used is qualitative with literature study techniques by collecting scientifically designed references and references that align with the research objectives. The data analysis used in this research is content analysis. The results of this study are as follows: 1) The substitution of the word faith is repeated in the Qur'an so that it can be understood that faith is essential in human life, as well as being the primary key in shaping one's Islam and personality. 2) Mental health is part of the psychology of religion, so the role of religion is according to that embraced by Muslims; namely, Islam can help humans achieve a mentally healthy condition by treating the soul and preventing mental disorders. Several ways to achieve a healthy personality, namely prayer, dhikr, reading the Koran, fasting, and pilgrimage. 3) The believer will be free from fear, panic, and complaints and adorned with patience and truth. It will be accessible from a stingy and greedy soul for worldly matters, adorned with glory and generosity. Will be free from the snares of lust, the seduction of satan, and anger, adorned with muqarabah to Allah, sincere to Him, and always asking for His help